The validation of the Turkish version of Asthma Control Test (vol 22, pg 1773, 2013) - Uysal, Mehmet Atilla; Mungan, Dilsad; Yorgancioglu, Arzu; Yildiz, Fusun; Akgun, Metin; Gemicioglu, Bilun; Yilmaz, Veysel (Springer, 2013)
[Abstract Not Available]